HUBUNGAN BEBAN KERJA, DURASI KERJA DAN SHIFT KERJA DENGAN KELELAHAN KERJA PADA PEKERJA PRODUKSI PT X SAMARINDA - Muhammad Rangga Danu Putra; Muhammad Sultan; Lestari, Ida Ayu Indira Dwika; Iwan M Ramdan; Dewi Novita Hardianti (Health Safety Environment, 2025)
Background: Workplace accidents caused by work fatigue remain relatively high and continue to increase annually. Work fatigue is often triggered by excessive workloads, with work duration and shifts also playing a significant role in contributing to fatigue in the workplace. This study aims to determine the relationship between workload, work duration, and work shifts with work fatigue among production workers at PT X Samarinda. Methods: This is a quantitative study with a cross-sectional design. The total sampling method was used, involving 60 respondents. Data were collected through direct questionnaires and analyzed using the Spearman Rank test. Results: The statistical analysis revealed a p-value of 0.081 for the relationship between workload and work fatigue, a p-value of 0.001 for the relationship between work duration and work fatigue, and a p-value of 0.001 for the relationship between work shifts and work fatigue. Conclusion: Work duration and work shifts have a more significant impact on work fatigue compared to workload. It is recommended that workers manage their break time effectively and increase their water intake during work, considering the hot working environment, to maintain productivity and prevent incidents.